Antiproliferative Activity of Ethanolic Extract of Ciplukan Herbs (Physalis angulata L.) on 7,12-Dimethylbenz[A]Nthracene-Induced Rat Mammary Carcinogenesis - Ameilinda Monikawati; Sofa Farida; Laras Widawaty Putri; Yurista Gilang Ikhtiarsyah; Edy Meiyanto (Indonesian Society for Cancer Chemoprevention, 2011)
Physalis angulata L. is an annual herb widely used as popular medicine for the treatment of cancer. Physalis angulata L. ethanolic extract (PEE) has been demonstrated to have strong cytotoxic activity against breast cancer, inhibited cancer cell’s proliferation and induced cell cycle arrest. The aim of our study is to investigate the effect of PEE as a cancer chemopreventive agent on 7,12-dimethylbenz[a]nthracene (DMBA)-induced rats mammary. The antiproliferative activity was characterized by monitoring the histopatology representation and expression of cell proliferation on DMBA-induced mammary rats that were treated with PEE against control groups. The histopatology representation were analyzed by Haematoksilin Eosin (HE) staining method, while proliferative activity was detected by AgNOR method. The HE staining results showed significant differences in cells morphology of treatment groups compared to the control groups. Thus results suggest that PEE was able to repair morphology of cells undergoing carcinogenesis. AgNOR method showed decreasing occurrence of black dots between treatment and control groups. Thus, we conclude that PEE has an antiproliferative activity on DMBA-induced rat mammary. Therefore, the ethanolic extract of Physalis angulata herbs is a potential chemopreventive agent on cancer. Further study on its molecular mechanism needs to be explored.Keywords: Physalis angulata, breast cancer, 7,12-dimethylbenz[a]nthracene, carcinogenesis, antiproliferative